A Pilot Study of Neural Correlates of Loss of Control Eating in Children With Overweight/Obesity: Probing Intermittent Access to Food as a Means of Eliciting Disinhibited Eating. (14th February 2018) - Goldschmidt, Andrea B; Dickstein, Daniel P; MacNamara, Annmarie E; Phan, K Luan; O'Brien, Setareh; Le Grange, Daniel; Fisher, Jennifer O; Keedy, Sarah
Abstract: Objective: Neural substrates of loss of control (LOC) eating are undercharacterized. We aimed to model intermittent access to food to elicit disinhibited eating in youth undergoing neuroimaging, given evidence that restricted food access may increase subsequent food intake via enhancing reward value of food and diminishing eating-related self-control. Methods: Participants were 18 preadolescents (aged 9–12 years) who were overweight/obese with recent LOC eating (OW-LOC; n  =   6); overweight/obese with no history of LOC eating (OW-CON; n  =   5); or non-overweight with no history of LOC eating (NW-CON; n  =   7). Participants underwent functional magnetic resonance imaging during a simulated food restriction paradigm in which they were alternately given restricted or unrestricted access to milkshake solutions. Results: There were no significant main effects of restricted versus unrestricted access to milkshake flavors. Group main effects revealed increased activation for OW-LOC relative to OW-CON in areas related to attentional processes (right middle frontal gyrus), inhibitory control/attentional shifts (right and left cuneus), and emotion regulation (left cingulate gyrus); and for OW-LOC relative to NW-CON in areas related to response inhibition (right inferior frontal gyrus). Significant block type × group interaction effects were found for the right middle frontal gyrus, left cingulate gyrus, and left cuneus, but these appeared to be accounted for primarily by group. Discussion: There were clear group differences in neural activity in brain regions related to self-regulation during a food restriction paradigm. Elevations in these regions among OW-LOC relative to OW-CON and NW-CON, respectively, may suggest that youth with LOC eating expended more cognitive effort to regulate ingestive behavior.